"Dando las Gracias a Mis Papás": Analyzing the Enactment of Callings across Generations of Latinx Immigrants. (24th September 2021) - Sánchez Sánchez, Virginia
Abstract: Callings, a prominent way in which communication scholars have spoken about meaningful work, are often used to describe individual pulls towards an occupation. Calling research has also been criticized for lacking participants with diverse backgrounds and occupations. This study addressed these gaps by investigating how Latinx immigrants across two generations made sense of their work as callings. By interviewing Latinx immigrants (N = 36) this study revealed that first- and second-generation immigrants co-constructed integrated callings. Unlike individual callings, integrated callings are tied to a common understanding of how various journeys are connected. Within immigrant families, there was an understanding about the relationship between first-generation immigrants' migration journeys and second-generation immigrants' occupational journeys. Across the two generations, work was tied to educational, occupational, and non-occupational outcomes that served to improve the lives of immigrants. The proposed framework, integrated callings, is one that accounts for non-occupational outcomes and the experiences of diverse workers.